Pendidikan Karakter Melalui Pembelajaran Berbasis Multiple Intelligences di Markaz Arabiyah Pare Kediri - Annas Ribab Sibilana (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
Character education is a grand issue which has been endeavored in various ways through education, so it is truly realized for the noble ideals of the Indonesian people. But what is happening right now in our education is the moral degradation of the children national character, so education has the task at the forefront to overcome this. Various methods have been conceived by experts and implemented one by one by the individual education, one of the latest methods and considered as an effective method by various education experts is through multiple intelligences approach. However, there are not many education implementers understand the concept, one of the institutions that dared to start implementing the concept is Markaz Arabiyah Pare Kediri, so researcher formulates a problem formulation of how the concept of learning based on multiple intelligences in Markaz Arabiyah and how the character education is implemented through the concept of learning. Markaz Arabiyah is the only institution in Pare Kediri that applies the theory of multiple intelligences starting from the process of accepting participants to the learning process, then from that process can also implement character education at the institution.